THE PRESENCE OF ROA AS A MODERATING VARIABLE IN THE EFFECT OF FOREIGN OWNERSHIP AND TRANSFER PRICING ON TAX AVOIDANCE - Muhammad Anwar Shubhan; Rita Yuniarti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Developing countries such as Indonesia are in dire need of state revenue to cover government expenditures in building infrastructure. Tax revenue in Indonesia is still considered not running optimally. This is because Indonesia's tax ratio is still relatively low, not reaching the standard level of tax ratio that should be for developing countries. Tax revenue is considered less than optimal due to cases of tax avoidance from business actions that take advantage of the loopholes in applicable tax regulations. This research aims to find out the influence of foreign ownership and transfer pricing on tax avoidance with ROA as a moderating variable using quantitative descriptive research methods. Statistical testing was carried out using panel data regression analysis with the help of Eviews software. The results of the study can be concluded that foreign ownership has no effect on tax avoidance, transfer pricing has an affects on tax avoidance, ROA is unable to moderate foreign ownership on tax avoidance, and ROA unable to moderate transfer pricing on tax avoidance